Performance and satisfaction level towards the maintenance of facilities in government buildings / Norzalikha Amirah Abdul Kadir - Abdul Kadir, Norzalikha Amirah (Faculty of Architecture, Planning and Surveying, 2015)
This paper focuses on the performance and satisfaction level occupants towards the maintenance of facilities. The purpose of this study was to determine the types of facilities that are commonly available in the building. The study was conducted on 90 user in three building which are Ministry of Finance, Ministry of Youth and Sports and Ministry of Rural Regional Development in Putrajaya. Instrument study involved a questionnaire containing 15 questions. The results showed which building performance and satisfaction level occupants towards the maintenance of facilities excellent or satisfactory. In addition, observation and interview session was also conducted to obtain performance of the maintenance in the building. Thus* it can be concluded some additional suggestions and proposals submitted to the facility as a guide for further studies.